Preparation of photoresponse n-Tio2 for hydrogen and oxygen evolution reactions in an electrochemical cell - Kow, Wei Khen
The objective of this final year project is to prepare photoresponse n-TiO2 for hydrogen and oxygen evolution reactions in an electrochemical cell. The objective is carried out by evaluating different composition of BaxSr1-xTiO3 as a photo-electrode towards the effectiveness of the solar hydrogen energy generating. This is done by determining the differences in the amount of voltage and hydrogen generated in the circuits of solar hydrogen cells.